Pengaruh sherd injuries terhadap general injuries pada siswa ekstrakurikuler bola basket - Alif Bagas Argawa Handoyo Putra; Prisca Widiawati; Muhammad Putra Ramadhan (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
This study aims to analyze the effect of Sherd Injuries on Ganeral Injuries in extracurricular basketball students of SMAN 8 Malang City. This research method uses One-Group Pretest-Posttest Design with experimental research design using quantitative descriptive research approach. In this study took a sample of 24 students consisting of 12 boys and 12 girls with the provisions of students who are active in participating in extracurricular basketball activities. The test used in data collection is the Functional Movement Screen (FMS). The results of this study indicate that the results of the leg muscle power test using the FMS test in female students get a significant value (p value < α = 0.001) while male students have a significant value (p value < α = 0.001). The conclusion that this study has a significant effect in the application of warm-up methods to reduce the risk of injury to athletes and achieve peak performance towards achievement. Keywords: Basketball, General injuries, Shre injuries